The influence of corporate governance on financial derivatives decisions - Tashfeen, Rubeena; Mahmood, Tashfeen; Mustafa, Faisal; Khursheed, Ambreen (Penerbit Universiti Kebangsaan Malaysia, 2022)
This study investigates corporate governance risk behavior around the financial crises period and its sensitivity to varying levels of financial constraints. The study employs simultaneous-equations methodology to examine firms’ capital structure and derivatives usage decisions simultaneously. The sample is split into high and low levels of financial risk to examine impacts of corporate governance on decisions regarding usage of derivatives under both conditions. Further, quantile analysis is preformed to investigate governance responses at different levels of risk. We observe that corporate governance responses vary with the levels of distress. At lower levels, insider shareholders, Chief Executive Officer (CEO) salary, and CEO age influence financial derivatives decisions. However, institutional shareholders, audit committee meetings, CEO bonus and other compensation consistently impact derivatives decisions, irrespective of the level of financial distress. The study suggests that governance mechanisms vary with financial distress levels. Firms could optimally structure their governance mechanisms accordingly. The study shows it is important to incorporate levels of risk in any corporate governance study.